Bridging imagination and strategy in SMEs: The role of ideas and strategy in SME performance - Adin Gustina; Jane S. Liu; Setyabudi Indartono; Nindya N. Laili (The Southern African Journal of Entrepreneurship and Small Business Management, 2025)
Background: Ideas have become the new battleground for small and medium enterprises’ (SME) success. In the digital age, competition is no longer focussed on information but on how they can compete to generate inventive ideas.